Планировка сабатиновских поселений, ее ландшафтная и социально-демократическая обусловленность - Черниенко, Ю.А.; Елисеев, В.Ф. (Материалы по археологии Северного Причерноморья, 2009)
This article is devoted to analysis of the planning of the Sabatinovka culture settlements. The linear (street) planning is most widespread. For it, the square permitting to build one or some lines of houses is practically sufficient (in North Pontic Area) landscape condition. Adaptation of such planning to building on slopes (the terraced type of building) is distinctive (Stepovoe and some other settlements). The dispersed type of building is possible only if the square for construction is sufficiently laige (the upper stratigraphical horizon of the settlement Schutskoe I). The compact building of large territories of some settlements, architectural blocks (block planning) are especially interesting. The settlement Vinogradniy Sad is situated on the narrow (100 m) terrace on the right bank of Yuzhniy Bug river. Compact and more spacious building is researched. On the north the settlement was limited by the steep cape. But ancient people were able to build spaciously down stream. Maybe, it was not desirable to move away from the granitic cliff near which the settlement was situated. But sometimes it is impossible to explain the compact building by landscape conditions in view of plenty of free squares (Voronovka II, Oktyabri I and so on). There were attempts to explain such planning by Aegean traditions. However, it was noted that it had widespread archaeological and ethnographical analogies. We may suppose that architectural blocks reflect something like ideological (maybe, patronimical) unity of their inhabitants. The large settlements of Sabatinovka culture with the compact planning have some quaziurban signs. But they were mainly agricultural settlements with indications of different level of development of nonfood production and were not integrating economic, politic or ideological centers of the whole districts, places of concentration of largest mass of population, palace or temple centers with the functions of concentration and redistribution of surplus products. That is why any Sabatinovka settlements may not be called by prototowns.